Analisis Efektivitas Arus Kas Sebagai Upaya Mengelola Piutang Tak Tertagih Dan Likuiditas Pada PT. Federal International Finance Kota Metro - Zanaria, Yulita; Darmayanti, Elmira Febri; Helmi, Masdar (Jurnal Manajemen DIVERSIFIKASI, 2023)
Cash flow, is an economic activity that is differentiated from the cash flow statement, whichis reported in the high balance sheet. Cash flow is usually not used to increase the cashaccount, but is used to pay dividends, increase inventory, fund trade receivables. Thisresearch aims to determine the effectiveness of managing cash receivables, determine theeffectiveness of cash flow policies and NPL policies in managing bad debts. The method usedis a quantitative method. Data collection techniques consist of observation, interviews andcompany data. Manage receivables with asset ratios and profitability ratios. The results ofthe research show that, the accumulation of the company's trade receivables indicates a lackof effectiveness in managing trade receivables and in the end the buildup of trade receivablescan hinder the acquisition of profitability ratios and high receivable turnover is acceptablefrom a liquidity perspective and can lead to higher returns on assets. tall.